Seamolec Training to Improve the Ability of TPACK Teachers in Adi Soemro's Space School - Sari, Muflihatul Laela; Maksum, Muh. Nur Rochim; Shohib, Muhammad Wildan; Shobahiya, Mahasri (Universitas Muhammadiyah Surakarta, 2023)
Purpose: Traning seamolec is an institution under the auspices of SEAMOE (Organization of Southeast Asian Ministers of Education) which facilitates research, improvement, courses and technology exchange within and outside the field of offline education and distance education (online) throughout Southeast Asia. The Ardhya Garini Foundation (YASARINI) which houses Space Schools throughout Indonesia including Sekolah Angkasa Lanud Adi Soemarmo collaborates with SEAMOE to facilitate teachers in improving TPACK skills through the seamolec training program. This research uses a qualitative research paradigm. In technical data collection using observation, interviews, and analysis. In this study, researchers used source triangulation techniques and trianggulation techniques to obtain valid data results. The result of this research is that seamolec training activities attended by Angksa Lanud Adi Soemamo school teachers succeeded in improving TPACK capabilities in the era of society 5.0. So that in the implementation of learning teachers can integrate pedagogical abilities and content into technology. In this way, it can be seen that the Angkasa Lanud Adi Soemarmo school teachers have qualified professionalism because they are able to keep up with technological developments in the era of society 5.0 through seamolec training.